PREDICTION OF HIGHER HEATING VALUE OF VARIOUS BIOMASSES USING THE EQUATION FOR THE HYDROTHERMAL CARBONIZATION METHOD ON BANANA BUNCHES - Sulaiman, Sani Maulana; Nugroho, Gunawan; Putra, Herlian Eriska; Fitria, Novi; Sukmawati, Wina Ike (Institut Teknologi Nasional, Bandung, 2024)
When designing many variables influence the thermal conversion system for homogeneous biomass and heterogeneous biomass. The factor that can have an important influence is the higher the calorific value (HHV). Many correlation models have been developed to estimate the HHV of homogeneous and heterogeneous biomass to reduce analysis costs. Unfortunately, the correlation model for predicting biomass HHV still has shortcomings when predicting biomass data from different thermal conversion processes and different types of biomass. In this study, four new correlations based on proximate and ultimate analysis of homogeneous biomass with the hydrothermal carbonization (HTC) method used for HHV prediction are presented. The multiple linear regression method is used to produce correlations from homogeneous biomass data then compare biomass models from open literature and compare correlation accuracy for data from the literature. It was found that the correlation obtained from proximate analysis (HHV =967.171 -8.684Ash -9.299VM -9.913FC) was more accurate than that obtained from proximate.